Method of Logical Synthesis of Integrated Circuits in basis K-PLA - Novikov, Sergey (Studia Informatica. System and information technology, 2006)
Modern Computer-Aided Design systems of Very Large Scale Integration allow to use the chips with thousands of components as element’s modules of electronic circuits. For example, ULSI - chip has complexity more than 20000 transistors. One of perspective chips (Programmable Logic Chip) has the architecture of a Programmable Logic Array (PLA). PLA can be programmed in a laboratory to perform complex functions with the help of a special equipment called by programmer (similar as PROM blower).